An Archeological Survey of Drainage District Number 17 Pumping Station Mississippi County, Arkansas. - Morse, Phyllis A. (1978)
A records check of the project area for known prehistoric sites showed no sites located. A physical inspection of the project area also showed no apparent cultural remains possibly due to heavy disturbance by levee building in the immediate area. Because of these negative results, no further investigation of the project area is warranted and project impact on cultural resources is negative